Non‐aneurysmal subarachnoid hemorrhage in 173 patients: a prospective study of long‐term outcome. (1st July 2015) - Konczalla, J.; Schmitz, J.; Kashefiolasl, S.; Senft, C.; Seifert, V.; Platz, J.
Abstract : Background and purpose: In some patients with subarachnoid hemorrhage (SAH) a bleeding source cannot be identified. Perimesencephalic (PM) SAH is assumed to have an excellent outcome. Our objective was to analyze the long‐term physical and psychological outcome of patients after non‐aneurysmal SAH. Methods: One hundred and seventy‐three patients met the inclusion criteria. Short‐term follow‐up 6 months after SAH was assessed according to the modified Rankin Scale (0–2 favorable). A short‐form health survey with 36 questions (SF‐36) and eight scales was used as questionnaire for long‐term follow‐up. Results: Thirty‐seven answers were received from the two groups, PM and non‐perimesencephalic (NPM) SAH, on average 76 months after ictus (range 1.5–14 years). PM‐ and NPM‐SAH without Fisher grade 3 blood pattern have excellent short‐term outcomes. The quality of life (QoL) is significantly reduced after non‐aneurysmal SAH, especially in NPM‐SAH. In particular, patients with a Fisher 3 blood pattern had significantly higher risks for cerebral vasospasm, delayed cerebral ischaemia, unfavorable outcome, reduced QoL and mortality in short‐ and long‐term follow‐up. Conclusions: Excluding rolph, only patients with a PM‐SAH have a similar QoL at long‐term follow‐up compared to the standard population. Patients with NPM‐SAH have a significantly decreased QoL in long‐term follow‐up. Furthermore, the Fisher 3 blood pattern group in particular had a significantly worse outcome − at short‐term and long‐term follow‐up. Therefore the NPM‐SAH group was stratified into patients with Fisher 3 blood pattern and patients without Fisher 3 in further investigations. Abstract : Clickhere for the corresponding questions to this CME article.